The Evaluation of Water Loss in The Western North Tarum Irrigation Channel - Tandiono, Felix; Yudianto, Doddi; Li, Ren; Ginting, Bobby Minola; Wicaksono, Albert; Fitriana, Finna; Fiona, Megan (JURNAL TEKNIK HIDRAULIK, 2024)
The Western North Tarum Irrigation channel plays a crucial role in supplying water to irrigated agricultural areas. However, it encounters challenges in ensuring adequate water delivery to all channel segments. This research assesses water loss during the distribution process in the Western North Tarum Irrigation channel, focusing on the evaluation of channel capacity and the impact of suboptimal water management on water loss. The study employs the HEC-RAS model, a hydraulic system analysis tool, to evaluate the channel’s capacity and simulates its behavior under various discharge conditions. The evaluation reveals that two channel segments, B.TUB 13 and B.TUB 25, have exceeded their capacity limits, resulting in overflow. Sedimentation downstream, particularly in these segments, exacerbates the issue by altering the channel slope and impeding water flow. This research identifies poor water distribution management as a significant factor contributing to water loss in the irrigation channel. Inadequate scheduling and the absence of proper water measurement tools result in instances of overwatering or underwatering in some areas. The lack of monitoring and control in the irrigation system hampers the detection of uncontrolled flow in the channels, leading to substantial water loss and inefficient water use. This research underscores the importance of evaluating and maintaining irrigation channel capacity to prevent overflow and water loss. Furthermore, it emphasizes the significance of effective water management to achieve more efficient water distribution and irrigation. Addressing these challenges is crucial for ensuring the long-term sustainability of irrigated agriculture in the Western North Tarum Irrigation area.Keywords: HEC-RAS, Irrigation Channel, Water Distribution, Water Loss, Western North Tarum